A note on ℋ3-algebras (1997)
In this note we shall generalize some results of the threevalued Lukasiewicz algebras to three-valued symmetrical Heyting algebras. We prove that a three-valued Heyting algebra with axe is a product of a Boolean algebra by a three-valued symmetrical Heyting symmetric algebra with center. We also introduce the involutive rough sets and we prove a representation theorem for three-valued symmetrical Heyting algebras by means of rough sets.